CENTRIFUGE TIME VARIATIONS ON RECALCIFICATION PERIOD VALUE - Mantu, Fathan; Warastuti, Rita Amini; Marlia (Journal of Health, Technology and Science (JHTS), 2024)
Hemostasis is the body’s mechanism to stop bleeding during an injury. The recalcification period examination is a specific hematological examination of blood clotting disorders to look for deficiency of clotting factors from the intrinsic pathway (Factors V, VIII, IX, X, XI, and XII), prothrombin and fibrinogen. According to the standard operating procedure (SOP), the examination of the recalcification period of the citrate blood centrifuge is 20 minutes at a speed of 3000 rpm. Based on the facts in the field, samples were taken simultaneously, and several different examinations were carried out so that when the centrifuge was carried out, it was not by the SOP. So that there can be an error in the production of the examined citrate plasma. The study aimed to determine the effect of centrifuge time variation on the value of the recalcification period. The research method uses a quantitative approach, experimental research, and a cross-sectional research design. The sampling technique is Accidental Sampling, using nine samples from 9 patients with 3 treatments. The results of the data normality test with the Shapiro-Wilk test from the test results carried out can be seen in 3 data groups; from the data obtained, there is one abnormal treatment. So, the Kruskal-Wallis Test was continued, and the Kruskal-Wallis test was non-parametric. The conclusion obtained from the study is that there is an influence on the recalcification period.